2014
DOI: 10.1007/s00300-014-1611-x
|View full text |Cite
|
Sign up to set email alerts
|

Food resource partitioning between three sympatric fish species in Porsangerfjord, Norway

Abstract: Understanding predator-prey relationships and resource overlap between sympatric species is fundamental for enhanced scientific knowledge and management. This study compared the trophic ecology of three small demersal fishes (Artediellus atlanticus, Myoxocephalus scorpius, and Leptagonus decagonus) using stomach data and stable isotope analyses. All fish were sampled during 2009-2011 from the inner basin of Porsangerfjord (70°N, 25°E) in northern Norway. The dominant prey found in A. atlanticus was polychaetes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 23 publications
0
6
1
Order By: Relevance
“…Although Shorthorn Sculpin have been documented with pelagic and demersal fishes in their gut contents (Kallgren et al 2014;Cardinale et al 2000) with some evidence that they feed on Arctic Cod (Dick et al 2009;Landry et al 2016) the results from this study are inconclusive regarding whether Shorthorn Sculpin actively prey on Arctic Cod, or scavenge them. The change in MTs in zone 1, a decrease in MT1 and increase in MT2, may be a result of Arctic Cod presence considering they occurred in much higher abundances and more often in zone 1 than in zones 2 and 3.…”
Section: Effects Of Arctic Cod Presence On Shorthorn Sculpin Movementcontrasting
confidence: 57%
See 1 more Smart Citation
“…Although Shorthorn Sculpin have been documented with pelagic and demersal fishes in their gut contents (Kallgren et al 2014;Cardinale et al 2000) with some evidence that they feed on Arctic Cod (Dick et al 2009;Landry et al 2016) the results from this study are inconclusive regarding whether Shorthorn Sculpin actively prey on Arctic Cod, or scavenge them. The change in MTs in zone 1, a decrease in MT1 and increase in MT2, may be a result of Arctic Cod presence considering they occurred in much higher abundances and more often in zone 1 than in zones 2 and 3.…”
Section: Effects Of Arctic Cod Presence On Shorthorn Sculpin Movementcontrasting
confidence: 57%
“…Shorthorn Sculpin are benthic and can reach a size of 30 cm, with a wide distribution from temperate to Arctic waters (Robins & Ray 1986). Their diets consist mainly of benthic invertebrates (Cui et al 2012), however, some juvenile and adult fishes have been identified in Shorthorn Sculpin stomachs (Kallgren et al 2014;Cardinale et al 2000), and stable isotope analysis has found that these fish couple benthic and pelagic energy pathways with as much as 50% of their consumed carbon coming from pelagic sources (McMeans et al 2013;Landry et al 2016). One study on the southern end of Baffin Island found Arctic Cod in the gut contents of Shorthorn Sculpin (Dick et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The value of P/B was set equal to that for small cod (1.20 year -1 ), while Q/B was set to 6.0 year -1 and was equal to the value used for small cod in the Sørfjord model (Pedersen et al 2008). The most common species in this group in Porsangerfjorden were shorthorn sculpin (Myoxocephalus scorpius) and Atlantic hookear sculpin (Artedillus atlanticus) (Källgren et al 2015). Shorthorn sculpin were distributed in the upper subtidal in all areas of the fjord and were also common at deeper water in the inner two subareas (4E and 4W).…”
Section: Group Namementioning
confidence: 99%
“…Separation between predatory species in the food niche dimension has been studied extensively in the ecological literature (e.g., Schoener, and references therein; Kamler, Stenkewitz, Klare, Jacobsen, & Macdonald, ; Domingo, Domingo, Badgley, Sanisidro, & Morales, ; Symes, Wilson, Woodborne, Shaikh, & Scantlebury, ; Sheremetev, Rozenfeld, Dmitriev, Jargalsaikhan, & Enkh‐Amgalan, ; Källgren, Pedersen, & Nilssen, ), and a general pattern of increased prey size with increasing predator size has been recognized, for example, in numerous guilds of birds, carnivorous mammals, lizards, wasps, flies, beetles, and marine predators (e.g., Hespenheide, and references therein; Cohen, Pimm, Yodzis, & Saldaña, ; Carbone, Mace, Roberts, & Macdonald, ; Brose et al., ; Costa, ; Nakazawa, and references therein). However, numerous factors affect actual prey intake, including prey availability, the environment, and intensity of competition (e.g., Herrera & Hiraldo, ; Kappes, Weimerskirch, Pinaud, & Le Corre, ; Levesque, Juniper, & Marcus, ; Luiselli, ; Tsuruta & Goto, ).…”
Section: Introductionmentioning
confidence: 99%